Predatory activity and nematocidal compounds released into liquid culture filtrates as attack strategies of a Mexican strain of Arthrobotrys oligospora against Haemonchus contortus infective larvae - Héctor Alejandro de la Cruz-Cruz; Rosa Isabel Higuera-Piedrahita; Yazmín Alcalá-Canto; Alejandro Zamilpa; Ana Yuridia Ocampo-Gutiérrez; Luis David Arango-de la Pava; Gerardo Ramírez-Rico; Génesis Andrea Bautista-García; Gustavo Pérez-Anzúrez; Agustín Olmedo-Juárez; María Manuela Reyes-Estebanez; Pedro Mendoza de Gives (PLoS ONE, 2026)
Nematophagous fungi offer a sustainable alternative for controlling nematode infections in small ruminants. The aims were to isolate and characterize both morphological and molecular nematophagous fungi from soil, to assess their predatory activity and the nematocidal activity of their liquid culture filtrates (LCF) against Haemonchus contortus infective larvae (L3), and to identify the protease activity of the LCF and mycoconstituents. The isolated and characterized Arthrobotrys oligospora was identified using both morphological and molecular techniques, with a similarity of 98%. Additionally, the isolated strain showed 89% phylogenetic similarity in the phylogenetic tree concerning the Arthrobotrys order. The A. oligospora isolate exhibited 72.06% predatory activity, and the liquid filtrate demonstrated 96.10% nematocidal activity at 100 mg/mL after 48 hours post-exposure against H. contortus infective larvae. Regarding enzyme activity, A. oligospora showed metalloprotease and cysteine-protease activities, and the zymogram revealed that these activities were higher under acidic conditions (pH 5).